Ni–Rh-based bimetallic conductive MOF as a high-performance electrocatalyst for the oxygen evolution reaction - Zu, Shu; Zhang, Huan; Zhang, Tong; Zhang, Mingdao; Song, Li (Frontiers in Chemistry, 2023)
Metal-organic frameworks (MOFs) have recently been considered as the promising catalysts due to the merits of abundant metal sites, versatile coordination groups and tunable porous structure. However, most MOFs suffer from low electronic conductivity, obstructing their application in electrocatalysis. In this work, we make fabricate a Ni-Rh bimetallic conductive MOF ([Ni2.85Rh0.15(HHTP)2]n/CC), in situ grown on carbon cloth. Abundant nanopores in the conductive MOFs expose additional catalytic active sites and advantageous 2D π-conjugated structure helps to accelerate charge transfer. Owing to the introduction of Rh, [Ni2.85Rh0.15(HHTP)2]n/CC exhibited substantially improved OER activity and exhibited only an overpotential of 320 mV to achieve 20 mA cm-2. The remarkable OER performance confirmed by the electrochemical tests could be ascribed to the synergistic effect caused by the doped Rh together with Ni in [Ni2.85Rh0.15(HHTP)2]n/CC, thereby exhibiting outstanding electrocatalytic performance.